What's in a weed's name? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1998)
Joël J. Loumeto, of the Botany and Ecology Laboratory at the Science Faculty in Brazzaville, Congo, writes about the number of names given to Chromolaena odorata (Spore 72, p. 4). 'The fact that there are so many underlines the importance of the...